Matemática
eduardamacedo
8

Determine o conjunto solução da equação 3^ (2x-1) - 3^(x) - 3^(x-1) + 1=0

+0
(1) Respostas
MATEUSMÁTICA

         3^ (2x-1) - 3^(x) - 3^(x-1) + 1 = 0   3^2x - 3^(x) - 3^x + 1 = 0     mmc = 3    3                 3    3^2x - 3.3^(x) - 3^x + 3 = 0    3^2x - 4.3^(x)  + 3 = 0                  3^x = a      a² - 4a + 3 = 0 Δ = 4  x1= 3   ; x2 = 1 Calculo de x :      3^x1 = a1 ==>    3^x = 3^1 ==> x = 1    3^x2 = a2 ==>    3^x2 = 1 ==>3^x2 = 3^0==> x = 0            V = { 0, 1 }

Adicionar resposta